2007
DOI: 10.5694/j.1326-5377.2007.tb00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Animal and human bite injuries in Victoria, 1998–2004

Abstract: Objective: To describe the epidemiology of mammal (human and non‐human) bite injuries in Victoria. Participants, design and setting: Retrospective case series of injuries recorded in the Victorian Emergency Minimum Dataset (VEMD) (1998–2004) and deaths recorded in the National Coroners Information System (1 July 2000 – 1 June 2006). Main outcome measures: Frequency, nature and outcome of injury as a function of mammal, victim demographics and season. Results: Of 12 982 bite injuries identified in the VEMD, dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 17 publications
6
34
0
1
Order By: Relevance
“…The same age group also had increased chances of suffering bite by owned dogs compared to unowned dogs. These findings are similar to previous studies that reported dog bites to be a major public health problem worldwide especially among male children below the age of 15 years [2, 4, 9, 13]. This is very critical in rabies elimination strategy using mass dog vaccinations since this age group are the ones who normally bring dogs for vaccinations (authors observation) and they are also critical group for targeting public health education to prevent rabies transmission following an incident of animal-bite including wound washing with soap and water, access to PEP and responsible dog ownership.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The same age group also had increased chances of suffering bite by owned dogs compared to unowned dogs. These findings are similar to previous studies that reported dog bites to be a major public health problem worldwide especially among male children below the age of 15 years [2, 4, 9, 13]. This is very critical in rabies elimination strategy using mass dog vaccinations since this age group are the ones who normally bring dogs for vaccinations (authors observation) and they are also critical group for targeting public health education to prevent rabies transmission following an incident of animal-bite including wound washing with soap and water, access to PEP and responsible dog ownership.…”
Section: Discussionsupporting
confidence: 92%
“…Approximately 85 to 90% of human animal-bite injuries are caused by dogs, 5 to 10% by cats and 2 to 3% by humans and rodents [2]. In low income countries, several studies have demonstrated that dogs account for 76 to 94% of animal-bite injuries resulting into high prevalence of rabies and higher fatality rates due to poor access to anti-rabies post exposure treatment [5–7].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that a greater number of human bites occurred among men than women is similar to those of other reports [10,13]. The propensity for men to be bitten by dogs was considered esplainable by the tendency of men to be more aggressive with dogs [7].…”
Section: Discussionsupporting
confidence: 83%
“…The hallmark of a boar attack is the infliction of multiple penetrating injuries to the lower part of the body [9]. In a study of mammalian injuries, the hands and wrists are the most commonly involved sites as 36.1%, followed by the face, head and neck (22.6%), and the arms (13.7%) [10]. …”
Section: Discussionmentioning
confidence: 99%